EFFECT OF ANNEALING ON MICROSTRUCTURE AND HARDNESS OF FeNiCo ALLOYS SYNTHESIZED BY MECHANICAL ALLOYING - Sutrisna, Sutrisna; Pamuji, Didit Setyo; Prasetiyo, Angger Bagus; Ababil, Ismail Zulpria; Aziz, Ihwanul (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Alloys based on Fe-Ni-Co are categorized as special nickel-based superalloys with braod application as magnetic sensors in electric motors, recording devices as well as for vehicle engine parts. The purpose of this study was to determine the physical and mechanical properties of Fe-Ni-Co materials synthesized by mechanical alloying method, then subjected to annealing temperature variation i.e 800oC, 900oC, and 1000oC for 1 hour. Test methods carried out by XRD-spectra to identify the phase, SEM and EDS mapping to determine the microstructure and composition together with micro hardness test to represent the mechanical properties of this FeNiCo alloys. The results of the XRD test showed that Co atoms and some Fe dissolved into the Ni crystal lattice tended to form a solid solution of g-Ni(Fe,Co). Microstructural observations at 900 OC after milling for 16 hours showed a fine and homogeneous grain structure. The highest hardness value was 421.5 kg/mm2 at 16 hours milling. The Fe-Ni-Co alloy exhibited a homogeneous microstructural distribution with a fine grain structure and high densification.